Impact of Macroeconomic Indicators on the Yuan-SDR Exchange Rate - Bhowmik, Debesh (Asian Journal of Empirical Research, 2021)
The paper endeavours to explore the macroeconomic impact on the Yuan SDR exchange rate of China during 2017m1-2021m6 to justify the internationalization of RMB which had entered into the SDR basket of IMF in October 2016.To evaluate the impact ,the paper used the methodology of Johansen (1988) cointegration and vector error correction model considering monthly Yuan per SDR as dependent variable and monthly GDP, inflation rate, foreign exchange reserves, export and import as the independent macro-economic variables. The pattern of trendline of Yuan per SDR is found nonlinear having cyclical fluctuations and seasonal variations according to Hamilton (2018). The paper also found that Yuan per SDR has significant long run causalities with export, import, inflation rate, GDP and foreign exchange rate of China during the specified period. Even, Yuan per SDR has significant short run causality with export only. The cointegrating equation converged towards the equilibrium with the speed of adjustment 11.83% per month significantly. The impulse response function of import to Yuan per SDR showed significantly convergent. The VECM contains autocorrelation problem and unit root for which it is non-stationary.